Welcome to your Simplifying Algebraic Expressions(Study by Topics Junior Class) NAME EMAIL PHONE NUMBER 1. Expand this (3a + 2)²2. Make y the subject of formula x = a+y/ a-y y = ax-1/ x+1 y = ax/ a+1 y = 2a-x/ a+x y = a(x-1)/ x+13. ’Simplify: ax³ + bazx² + cxa Axb(x + zx + c) xX(ax + ba + ca) ax(x² + bzx + c) X(ax + ba + ca)4. Make y the subject of the relation cd/ a(c-d) c-d/ acd c+d/ a(c-d) c-d/ a(c+d)5. What number is known as the multiplicative identity?6. Simplify; 2x + 5y - 7x + 8y 5x + 3y -5x + 13y -5x + 3y 9x + 13y7. 4(x + 8) - 9 4x + 24 12x - 9 4x + 23 4x + 328. 9ab × 6a 56a²b 54ab 54a²b 48a²b 76a²b9. Make b the subject of formula b = a-c³/ cd² b = cd²/ a-c³ b = cd/ a-c³ b = d²/ a-c²10. ^{1}/_{3} of 48y 16y 18y 12y 24y11. What is the algebraic expression to represent y less than twenty Y + 20 20 + 20 - y Y - 2012. Expand (2x - 3y + z)(3x - y+ 4z) 6x² - 11xy - 3y² + 4z² + 3xz - 12yz 6x² - 2xy + 3y² + 4z² + 11xz - 13yz 6x² - 11xy + 3y² + 4z² + 11xz - 13yz 6x² - 9xy + 3y² + 4z² + 8xz - 12yz13. Simplify (12x - 7y) + (6y + 3x) 15x - 13y 15x - y 15x + 13y 12x - y14. -3(x + y) + 5(x - y) 2x - 8y -2x + 2y 8x - 8y 2x - 8y15. The quantity Q varies inversely as p; p varies directly as the square root of r, and r varies directly as 1/t².Then Q varies inversely as t Q varies directly as t² Q varies inversely as t² Q varies directly as t16. Simplify: 8a - 3(2a - 3b) 2a + 3b 2a + 9b 5a - 9b 2a - 9b17. 6a × 3 9a 18a 20a 15a 8a18. X varies inversely as y and y varies directly as t². Find the relationship between X and t given that t = 7 when X = 2 Xt² = 98 X = 98t² 98Xt² = 1 X = t²/9819. Divide y³ - 2y² - 5y + 6 by (y - 1) y² - 7y + 6 y²- y - 6 y² - 5y + 6 y² - 5y - 620. Simplify the expression: (3a + b) - (2a - 2b) 5a - 3b a - b a - 3b 5a + 3b a + 3b21 out of 20Time is Up!